1997
DOI: 10.1017/s030500099600298x
|View full text |Cite
|
Sign up to set email alerts
|

The Contrast Theory of negative input

Abstract: Beliefs about whether or not children receive corrective input for grammatical errors depend crucially on how one defines the concept of correction. Arguably, previous conceptualizations do not provide a viable basis for empirical research (Gold, 1967; Brown & Hanlon, 1970; Hirsh-Pasek, Treiman & Schneiderman, 1984). Within the Contrast Theory of negative input, an alternative definition of negative evidence is offered, based on the idea that the unique discourse structure created in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
218
4
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(236 citation statements)
references
References 25 publications
10
218
4
4
Order By: Relevance
“…showed that corrective recasting, which includes a recast preceded by a repetition of the learner's error and intonational stress added to both repetition and recast to emphasize the incorrect and correct forms, is also more effective than no feedback+ Ohta~2000! showed that four adult learners who produced private speech with moderate to high frequency while wearing lapel microphones in a formoriented foreign language classroom tended to repeat recasts, regardless of whether they were the intended recipients of the recasts~cf+ Nabei & Swain, 2002!+ For a comprehensive review of recast studies, see Nicholas, Lightbown, and Spada~2001!+ Based on my own observation studies of immersion classrooms~e+g+, Lyster, 1998bLyster, , 2002b have argued that recasting-as defined in the L1 literature~e+g+, Marcus, 1993;Saxton, 1997! and as observed in immersion classrooms i+e+, an implicit targetlike reformulation of a learner's utterance!-is not the most effective way of providing young L2 learners with negative evidence in classrooms where the primary focus is on subject matter, especially in comparison with other feedback options+ My analyses of immersion classroom discourse suggested that recasts are, for the most part, embedded in meaningfocused negotiation and are thus ideal for facilitating the delivery of complex subject matter, because they provide supportive, scaffolded help, which serves to move the lesson ahead when the target forms in question are beyond the students' current production abilities+ Recasts used in this way compete with many other demands on attention during content-based instruction and appear to be ambiguous, because they share discourse functions with a similar proportion of teacher repetitions of well-formed utterances~Lyster, 1998b!…”
Section: Recasts and Promptsmentioning
confidence: 99%
“…showed that corrective recasting, which includes a recast preceded by a repetition of the learner's error and intonational stress added to both repetition and recast to emphasize the incorrect and correct forms, is also more effective than no feedback+ Ohta~2000! showed that four adult learners who produced private speech with moderate to high frequency while wearing lapel microphones in a formoriented foreign language classroom tended to repeat recasts, regardless of whether they were the intended recipients of the recasts~cf+ Nabei & Swain, 2002!+ For a comprehensive review of recast studies, see Nicholas, Lightbown, and Spada~2001!+ Based on my own observation studies of immersion classrooms~e+g+, Lyster, 1998bLyster, , 2002b have argued that recasting-as defined in the L1 literature~e+g+, Marcus, 1993;Saxton, 1997! and as observed in immersion classrooms i+e+, an implicit targetlike reformulation of a learner's utterance!-is not the most effective way of providing young L2 learners with negative evidence in classrooms where the primary focus is on subject matter, especially in comparison with other feedback options+ My analyses of immersion classroom discourse suggested that recasts are, for the most part, embedded in meaningfocused negotiation and are thus ideal for facilitating the delivery of complex subject matter, because they provide supportive, scaffolded help, which serves to move the lesson ahead when the target forms in question are beyond the students' current production abilities+ Recasts used in this way compete with many other demands on attention during content-based instruction and appear to be ambiguous, because they share discourse functions with a similar proportion of teacher repetitions of well-formed utterances~Lyster, 1998b!…”
Section: Recasts and Promptsmentioning
confidence: 99%
“…Doughty (1998) Saxton's (1997, p. 155) Saxton (1997) demonstrated in an experiment which manipulated the input to children acquiring irregular past tense forms that the children were able to recover from overgeneralized hypotheses when given recasts oferrors better than when provided positive input models in advance oftheir errors. This advantage for recasts over models has also been found for Ll English learners ofl,2 Spanish adjective placenrnt (Ortega & Long, 1997 …”
Section: Cognitive Underpinnings Of Focus On Form 43mentioning
confidence: 99%
“…As in the case of the positive evidence, the immediate effect of the negative evidence in Saxton's (1997) sense was not observed for accusative case-marking. However, both positive evidence and the negative evidence had a certain effect on the children's utterances.…”
Section: Resultsmentioning
confidence: 69%
“…Adult: He shot the fish! According to Saxton (1997), the negative evidence provided immediately after the child's error highlights the contrast between the child's error and the correct form. His experimental study demonstrates that English-speaking children can learn the irregular past tense form of novel verbs when negative evidence is given.…”
mentioning
confidence: 99%